COMMUNITY-BASED CATARACT EDUCATION: THE ROLE OF THE ‘SEKAR’ PKK GROUP OF GARUNG VILLAGE, WONOSOBO IN MAINTAINING EYE HEALTH - Sahli, Muhamad; Raharyani, Anisa Ell (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Background: Cataract is one of the leading causes of visual impairment and blindness, particularly among the elderly population, with a higher incidence observed in women. Limited public knowledge regarding cataract risk factors, symptoms, and management often results in delays in eye examinations and treatment. Objective: This community service activity aimed to improve the knowledge and understanding of members of the PKK “Sekar” group in Garung Village regarding cataracts, including their definition, risk factors, symptoms, prevention, and management. Methods: The activity employed a health education approach through interactive lectures, discussions, and question-and-answer sessions, supported by educational media such as PowerPoint presentations, leaflets, and posters. Knowledge evaluation was conducted using pre-test and post-test questionnaires. The activity was conducted on November 18, 2025, involving 20 participants. Results: The evaluation results demonstrated a significant improvement in participants’ knowledge, as indicated by an increase in the mean knowledge score from 81 in the pre-test to 98 in the post-test. Conclusion: Health education delivered through a PKK group-based approach was proven to be effective in enhancing community knowledge, particularly among elderly women, regarding cataracts. This activity serves as a promotive and preventive effort to reduce the risk of visual impairment and blindness caused by cataracts.